Optical, luminescence, and energy transfer studies of Gd3+/Dy3+ doped potassium gadolinium borophosphate glasses. (November 2022) - Khrongchaiyaphum, F.; Wantana, N.; Sarumaha, C.S.; Kaewnuam, E.; Kothan, S.; Chanthima, N.; Kaewkhao, J.
Abstract: The K2 O–Gd2 O3 –B2 O3 –P2 O5 glass doped with Dy2 O3 (Dy:KGPB) were synthesized by the melt-quenching technique. These glasses were subjected to characterize the physical, structure, optical and luminescence properties. It was observed that the density, molar volume and refractive index of glass increased with increasing Dy2 O3 concentration. The FTIR result confirmed the main glass network of BOB and POP linkages those were degraded by adding Dy2 O3 modifier. Glasses absorbed photons in ultraviolet, visible light and near-infrared region. The photoluminescence under direct Dy 3+ excitation performed the strong emissions at 574 and 482 nm corresponding to 4 F9/2 → 6 H13/2 and 4 F9/2 → 6 H15/2 transition, respectively. The Gd 3+ excitation also caused strong emission of Dy 3+ by the Gd 3+ -Dy 3+ energy transfer. Glass doped with 1.00 mol% of Dy2 O3 owned the highest emission intensity due to the concentration quenching. The lifetime of 4 F9/2 level was found to decrease with addition of Dy2 O3 content via dipole-diploe interaction between Dy 3+ ion. Judd-Ofelt (J-O) intensity parameters were initially calculated and applied to evaluate the radiative parameters such as branching ratios, radiative transition probabilities, and stimulated emission cross-sections. The radioluminescence of glass was also investigated and found the scintillation efficiency around 15.6%, compared to BGO scintillator. The Dy:KGPB glass has an interesting potential for solid-state laser, LED and X-ray detection applications. Highlights: The energy transfer phenomenon was observed from Gd 3+ -Dy 3+ ions. The bright greenish-yellow emission was observed for present glasses. Energy transfer parameter show increasing trend with increase in Dy 3+ ions. X-rays scintillation efficiency of glass was 15.6% compared to BGO scintillator. CIE chromaticity diagram show greenish-yellow emission under UV lamp excitation.